Inovasi Media Pembelajaran Berbasis Problem Based Learning pada Bidang Elektronika Analog Digital - Agry Berlianda Putri; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to produce innovations in the form of interactive, valid and practical learning media, and can support the Problem Based Learning (PBL) method in Analog and Digital Electronics courses. The research method used is the Pre-Experimental method with One Shot Case Study design. The subject of this research is Analog and Digital Electronics course. This learning media innovation was applied to several students of the Electrical Engineering Department, Faculty of Engineering, Universitas Negeri Padang, in 2021 who were taking Analog and Digital Electronics courses. Before being shown to respondents, the learning media is tested for validity/feasibility by media expert lecturers. In view of the feasibility test that has been done, this learning media gets a value of ninety three percent, both with regards to appearance and content of the material. Thus, the media can be declared valid/valid so that the research can be continued in obtaining the value of the practicality of the media from the respondents who have been given treatment. The practicality test which was filled out by eight students, obtained an average data of ninety two percent in the very practical category. Data on the feasibility and practicality of the media were obtained using a validated questionnaire of zero point ninety eight by instrument expert lecturers. So, it tends to be inferred that the learning media in the Analog and Digital Electronics course is valid and practical to use in the Analog and Digital Electronics learning process.